Conference on Lasers and Electro-Optics 2020
DOI: 10.1364/cleo_at.2020.aw3i.2
|View full text |Cite
|
Sign up to set email alerts
|

Active and Ultrasensitive Chemical and Biosensing through Optothermally Generated Microbubble

Abstract: Rapid and sensitive detection of harmful chemicals or biological samples is essential for medical study and industrial applications. For example, in the food industry, it is an urgent demand to detect hazardous chemicals or pathogens and then efficiently eliminate contaminated sources from the food production chain to protect people from toxic food-borne infection. In addition, toxic chemicals, pesticides and pathogens are also responsible for water, air and soil contamination. Therefore, rapid and sensitive d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 101 publications
0
2
0
Order By: Relevance
“…Several proof-of-principle applications based on bubble-induced flow have been demonstrated, such as increasing the detection rate of surface-based sensors , and manipulating nanostructures. , However, in most of these studies, the created bubbles were tens to hundreds of microns in size. Such large bubbles do not allow for rapid and dynamic flow control because of the diffusion limited slow expulsion of dissolved gas, accumulated in the bubble from the surrounding water, after illumination has ceased. , Though the bubble lifetime can be decreased by using degassed water, , this is not feasible in most practical applications. , As a solution to this issue, Jones et al recently demonstrated that spatially isolated gold nanoantennas are able to produce micron-sized bubbles that can be modulated at up to kHz frequencies in air-equilibrated water. , The reason for this is that it is now the spatial extension of the plasmonic antenna that determines the bubble size rather than the illuminated area, as in previous experiments with distributed plasmonic arrays. Furthermore, it was found that a very strong transient, producing mm/s flow velocities close to the antenna, is induced as a microbubble form .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several proof-of-principle applications based on bubble-induced flow have been demonstrated, such as increasing the detection rate of surface-based sensors , and manipulating nanostructures. , However, in most of these studies, the created bubbles were tens to hundreds of microns in size. Such large bubbles do not allow for rapid and dynamic flow control because of the diffusion limited slow expulsion of dissolved gas, accumulated in the bubble from the surrounding water, after illumination has ceased. , Though the bubble lifetime can be decreased by using degassed water, , this is not feasible in most practical applications. , As a solution to this issue, Jones et al recently demonstrated that spatially isolated gold nanoantennas are able to produce micron-sized bubbles that can be modulated at up to kHz frequencies in air-equilibrated water. , The reason for this is that it is now the spatial extension of the plasmonic antenna that determines the bubble size rather than the illuminated area, as in previous experiments with distributed plasmonic arrays. Furthermore, it was found that a very strong transient, producing mm/s flow velocities close to the antenna, is induced as a microbubble form .…”
Section: Introductionmentioning
confidence: 99%
“…Several proof-of-principle applications based on bubbleinduced flow have been demonstrated, such as increasing the detection rate of surface-based sensors 12,13 and manipulating nanostructures. 14,15 However, in most of these studies, the created bubbles were tens to hundreds of microns in size.…”
Section: ■ Introductionmentioning
confidence: 99%